A very rare complication of frontal sinusitis: Pott’s puffy tumor - Parlak, Furkan; Bahceci, Busra; Cam, Betul; Uzun, Ozlem; Coskun, Abuzer (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Pott’s puffy tumor is a very rare clinical condition characterized by subperiosteal abscess, a complication of frontal sinusitis, or as a result of head trauma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Early diagnosis of this condition is significantly important to prevent sequelae and severe neurological complications. This phenomenon, which is generally seen in children, can rarely be encountered in adults. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. In this report, we share a rare case of Pott’s puffy tumor in an adult patient. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Pott’s puffy tumor, a rare complication of frontal sinusitis, should be considered to prevent neurological and intracranial complications.